Feasibility study on the use of single-crystalline PV Installations in Cyprus - Panayiotou, Gregoris; Koukkouli, A.; Kalogirou, Soteris A. (My University, 2010)
The objective of this work is to evaluate the Current and the New Subsidisation schemes in Cyprus by simulating a series of different scenarios for grid-connected single-crystalline PV system applications in both seaside and inland locations. This is done in order to obtain a more realistic and specific view on which option gives the most economically profitable benefits for each case. The locations considered are that of the cities of Pafos, Larnaca and Nicosia and the examined installations’ power are 5, 20 and 150 kW. The simulation procedure was carried out using PVSyst®. The results of the simulation procedure indicate that the most profitable and viable option for all cases is the one with no initial subsidisation grant benefit and supply the produced energy to the grid for purchasing at a higher price. Finally, this feasibility study can be used for the preliminary evaluation of large PV system investments by taking into consideration the current prices of the PVs.
Keywords: New Subsidisation scheme; Cyprus; PV system; Feasibility study